Dexamethasone increases aquaporin-2 protein expression in ex vivo inner medullary collecting duct suspensions - Chen, Minguang; Cai, Hui; Klein, Janet D.; Laur, Oskar; Chen, Guangping (Frontiers in Physiology, 2015)
Aquaporin-2 (AQP2) is the vasopressin-regulated water channel that controls renal water reabsorption and plays an important role in the maintenance of body water homeostasis. However, whether and how glucocorticoid regulates AQP2 remains unclear. In this study, we examined the direct effect of dexamethasone on AQP2 protein expression and activity. Dexamethasone increased AQP2 protein abundance in rat inner medullary collecting duct suspensions. This was confirmed in HEK293 cells transfected with AQP2 cDNA. Cell surface protein biotinylation showed an increase of dexamethasone-induced cell membrane AQP2 expression and this effect was blocked by glucocorticoid receptor antagonist RU486. Functionally, dexamethasone treatment of oocytes injected with an AQP2 cRNA increased water transport activity as judged by cell rupture time in a hypo-osmotic solution (66 ± 13s in dexamethasone vs 101 ± 11s in control, n=15). We further found that dexamethasone treatment reduced AQP2 degradation, which could result in an increase of AQP2 protein. Interestingly, dexamethasone promoted cell membrane AQP2 moving to less buoyant lipid raft submicrodomains. Taken together, our data demonstrate that dexamethasone promotes AQP2 protein expression and increases water permeability mainly via inhibition of AQP2 protein degradation. The increase in AQP2 activity promotes water reabsorption, which may contribute to glucocorticoid-induced water retention and hypertension.